Immune Senescence Markers Predict the Cellular Immune Response to BNT162b2 Vaccination in Hemodialysis Patients. (31st October 2022) - Van Praet, Jens T; De Groote, Marie; De Bacquer, Dirk; Verhalleman, Ellen; Welvaert, Ziggy; Emmerechts, Jan; Reynders, Marijke; De Vriese, An S
Abstract: Background: Chronic kidney disease is associated with increased risk of frailty and accelerated immune senescence, potentially affecting the immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination. Methods: Humoral and cellular responses against the spike protein of SARS-CoV-2 were determined in 189 COVID-naive hemodialysis patients at week 4 and 8 after vaccination with 2 doses of BNT162b2. Frailty indicators and immune senescence markers were determined at baseline to identify predictors of the immune response. Results: Controlling for age, activities of daily living (ADLs), instrumental ADLs, walking pace, and the clinical frailty score correlated negatively and hand grip strength positively with the humoral response. Controlling for age, the proportions of memory CD4 + T cells, memory CD8 + T cells, CD28 null T cells, and CD57 + CD8 + T cells correlated negatively with the humoral response, whereas the proportions of memory CD4 + T cells and CD28 null T cells correlated negatively and the CD4/CD8 ratio positively with the cellular response. In a multivariate model, only the proportions of memory CD4 + T cells and CD28 null T cells independently predicted the cellular response. Conclusions: Markers of immune senescence, but not frailty indicators, independently predict the cellular immune response after vaccination in hemodialysis patients, overruling the effect of chronological age.